Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/pmic.202100312
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics‐driven identification of short open reading frame‐encoded peptides

Abstract: Accumulating evidence has shown that a large number of short open reading frames (sORFs) also have the ability to encode proteins. The discovery of sORFs opens up a new research area, leading to the identification and functional study of sORF encoded peptides (SEPs) at the omics level. Besides bioinformatics prediction and ribosomal profiling, mass spectrometry (MS) has become a significant tool as it directly detects the sequence of SEPs. Though MS-based proteomics methods have proved to be effective for qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 200 publications
1
7
0
Order By: Relevance
“…The function of SEPs can be validated by a genetic approach (knockdown and knockout) and determining the protein interaction by affinity purification mass spectrometry or proximity-labeling approach. 53 In summary, our results contribute to a deeper understanding of the S. cerevisiae proteome and provide supporting data for the functional characterization of SEPs responding to environmental stress. These SEPs might help understand the stress response and improve the fermentation usage of yeast.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The function of SEPs can be validated by a genetic approach (knockdown and knockout) and determining the protein interaction by affinity purification mass spectrometry or proximity-labeling approach. 53 In summary, our results contribute to a deeper understanding of the S. cerevisiae proteome and provide supporting data for the functional characterization of SEPs responding to environmental stress. These SEPs might help understand the stress response and improve the fermentation usage of yeast.…”
Section: Discussionsupporting
confidence: 59%
“…We found that many SEPs carried mitochondrial transfer peptides, suggesting that these SEPs might be functionally located in the mitochondria. The function of SEPs can be validated by a genetic approach (knockdown and knockout) and determining the protein interaction by affinity purification mass spectrometry or proximity-labeling approach . In summary, our results contribute to a deeper understanding of the S.…”
Section: Discussionmentioning
confidence: 80%
“…It should be noted that TDP for the analysis of SEPs employs many of the strategies developed for peptidomic analyses. 44 , 55 Essentially both TDP and peptidomics target (small) intact proteins/peptides without the use of enzymatic digestion and the differentiation between small protein and large peptide is largely semantic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sample preparation is a prerequisite for thorough analysis of PTMs proteins [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, owing to the weaker ionization efficiency of PTMs proteins than non‐PTMs proteins, the analysis and identification of samples is more difficult. Therefore, sample preparation is a prerequisite for thorough analysis of PTMs proteins [12–16].…”
Section: Introductionmentioning
confidence: 99%